2008
DOI: 10.1016/j.cell.2008.09.058
|View full text |Cite
|
Sign up to set email alerts
|

Structural Synergy and Molecular Crosstalk between Bacterial Helicase Loaders and Replication Initiators

Abstract: The loading of oligomeric helicases onto replication origins marks an essential step in replisome assembly. In cells, dedicated AAA+ ATPases regulate loading, however, the mechanism by which these factors help recruit and deposit helicases has remained unclear. To better understand this process, we determined the structure of the ATPase region of the bacterial helicase loader DnaC from Aquifex aeolicus to 2.7 Å resolution. The structure shows that DnaC is a close paralog of the bacterial replication initiator,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
214
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(223 citation statements)
references
References 64 publications
(83 reference statements)
8
214
1
Order By: Relevance
“…The influence of ATP on DnaC function has been an enigma, but new evidence suggests that its ATPase activity is activated at a specific step of the initiation process (see below). Stimulated by ATP, DnaC also interacts weakly with ssDNA (Learn et al 1997;Davey et al 2002;Mott et al 2008), supporting the idea that this activity may be involved in helicase loading. Because DnaC complexed to DnaB inhibits its ATPase and helicase activities (Wahle et al 1989a,b;Allen and Kornberg 1991;Davey et al 2002;Mott et al 2008), DnaC must dissociate from DnaB for helicase activation to occur.…”
Section: Dnac Controls the Activity Of Dnabsupporting
confidence: 50%
See 2 more Smart Citations
“…The influence of ATP on DnaC function has been an enigma, but new evidence suggests that its ATPase activity is activated at a specific step of the initiation process (see below). Stimulated by ATP, DnaC also interacts weakly with ssDNA (Learn et al 1997;Davey et al 2002;Mott et al 2008), supporting the idea that this activity may be involved in helicase loading. Because DnaC complexed to DnaB inhibits its ATPase and helicase activities (Wahle et al 1989a,b;Allen and Kornberg 1991;Davey et al 2002;Mott et al 2008), DnaC must dissociate from DnaB for helicase activation to occur.…”
Section: Dnac Controls the Activity Of Dnabsupporting
confidence: 50%
“…Early studies suggested that ATP bound to DnaC is necessary for DnaC to form an isolable complex with DnaB and to protect DnaC from inactivation by N-ethylmaleimide (Wickner and Hurwitz 1975;Kobori and Kornberg 1982). More recent studies indicate that ATP is not needed for DnaC to interact with DnaB (Davey et al 2002;Galletto et al 2003;Mott et al 2008). Both cryoelectron microscopy of the DnaB -DnaC complex in comparison with DnaB and fluorescence energy transfer experiments indicate that DnaC is bound to the larger (carboxy-terminal) end of the DnaB toroid (Bárcena et al 2001;Galletto et al 2003).…”
Section: Dnaa Is the Replication Initiator In Bacteriamentioning
confidence: 94%
See 1 more Smart Citation
“…The DnaA AAAϩ ATPase is the initiator of replication in bacteria and functions via multiple protein-protein or protein-DNA interactions (2,3,17). Its modular architecture allows for interactions with different binding partners during the various steps of the formation of the active replication forks and coupling to other cellular events (3,15,17,20,22,29,30).…”
Section: Discussionmentioning
confidence: 99%
“…The DnaA paralogue DnaC is necessary to load the DnaB helicase. DnaC can form helical structures and can specifically bind to ATP-DnaA (17). This suggests that in E. coli, DnaC is a molecular adaptor that uses DnaA as a docking platform to load DnaB on the replication fork (17).…”
mentioning
confidence: 99%